2018
DOI: 10.1016/j.jcf.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

IgG avidity to Pseudomonas aeruginosa over the course of chronic lung biofilm infection in cystic fibrosis

Abstract: IgG avidity to P. aeruginosa alginate does not significantly enhance as chronic lung infection progresses. This probably plays a role in the difficulty to mount an effective opsonophagocytic killing to clear mucoid P. aeruginosa infection in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Thus, IL17-γδ T cells may help the bacterial clearance and improve survival via innate and humoral immunity. However, Bayes et al suggested that pathogenesis was unaffected in mice lacking B cells [98], supporting the idea that an elevated humoral response during chronic P. aeruginosa infection is not associated with clinical improvement [102]. Indeed, it is suggested that the high expression of specific anti-P. aeruginosa IgG may lead to the formation of circulating immune complexes, which are deposited in the lower airways tissue, triggering tissue damage and long-term deterioration of lung function [102].…”
Section: The Adaptive Responsementioning
confidence: 99%
“…Thus, IL17-γδ T cells may help the bacterial clearance and improve survival via innate and humoral immunity. However, Bayes et al suggested that pathogenesis was unaffected in mice lacking B cells [98], supporting the idea that an elevated humoral response during chronic P. aeruginosa infection is not associated with clinical improvement [102]. Indeed, it is suggested that the high expression of specific anti-P. aeruginosa IgG may lead to the formation of circulating immune complexes, which are deposited in the lower airways tissue, triggering tissue damage and long-term deterioration of lung function [102].…”
Section: The Adaptive Responsementioning
confidence: 99%
“…B cells respond robustly to chronic P. aeruginosa infection through production of high levels of P. aeruginosa -specific IgG and IgA antibodies (Abs) and immune complex formation. However, this robust humoral response is not associated with bacterial clearance or clinical improvement and has even in some cases been suggested to be detrimental ( 257 , 258 ). Though B cell responses were some of the earliest characterized responses to chronic lung P. aeruginosa infection ( 259 , 260 ), they remain poorly understood to this day ( 257 ).…”
Section: Immune Response To Infectionmentioning
confidence: 99%
“…Moreover, bacterial communities embedded in an extracellular matrix (ECM) form biofilms. P. aeruginosa biofilms are more resistant to host responses than their planktonic counterparts, which makes it difficult to remove the biofilms [7,8]. In order to solve the problem of food corruption caused by P. aeruginosa, it is necessary to continuously develop and improve effective antimicrobial strategies.…”
Section: Introductionmentioning
confidence: 99%